Black Alice - Cadava, Eduardo (Columbia Journal of Gender and Law, 2014)
I promise to write a longer letter to you soon, but today I want to tell you about the three figures to which I have returned as I have thought of writing this letter to you and as I have been rereading your books these last days. I want to write to you about silence, water, and animals. In this way, I want to say something about what your work tells us about the essential interdisciplinarity of the law, something that, in your hands, prevents the law from ever being identical to itself, perhaps even tells us that what makes the law the law is that it can never be simply itself. Using an “intentionally double-voiced and relational, rather than a traditionally legal black-letter, vocabulary,” you say that your writing is “staked out as the exclusive interdisciplinary property of constitutional law, contract, African-American history, feminist jurisprudence, political science, and rhetoric,” something that already opens the law to its presumed others.